How to Identify Programming Skills from Source Code? - Oliveira, Johnatan (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2022: Anais do XXV Congresso Ibero-Americano em Engenharia de Software, 2022)
Both open-source and proprietary software systems have become increasingly complex. Despite their growing complexity and increasing size, software systems must satisfy strict release requirements that impose quality, putting significant pressure on developers. Therefore, the success of software projects is dependent on the identification and hiring of qualified developers to build a solid and cohesive team with different programming skills. Our main goal is to develop and evaluate a method able to compute programming skills from source code analysis. Our method uses software metrics such as Changed Files and Changed Lines of Code, to compute the skills. Our results showed that our method is able of identifying programming skills of the developers about mainly libraries used, programming languages, and profile concerning back-end & front-end and unit test.